Early childhood profiles of sleep problems and self-regulation predict later school adjustment - Williams, Kate E; Walker, S; Nicholson, Jan; Nicholson, J; Williams, Kate (My University, 2016)
BACKGROUND: Children's sleep problems and self-regulation problems have been independently associated with poorer adjustment to school, but there has been limited exploration of longitudinal early childhood profiles that include both indicators. AIMS: This study explores the normative developmental pathway for sleep problems and self-regulation across early childhood and investigates whether departure from the normative pathway is associated with later social-emotional adjustment to school. SAMPLE: This study involved 2,880 children participating in the Growing Up in Australia: The Longitudinal Study of Australian Children (LSAC) - Infant Cohort from Wave 1 (0-1 years) to Wave 4 (6-7 years). METHOD: Mothers reported on children's sleep problems, emotional, and attentional self-regulation at three time points from birth to 5 years. Teachers reported on children's social-emotional adjustment to school at 6-7 years. Latent profile analysis was used to establish person-centred longitudinal profiles. RESULTS: Three profiles were found. The normative profile (69%) had consistently average or higher emotional and attentional regulation scores and sleep problems that steadily reduced from birth to 5 years. The remaining 31% of children were members of two non-normative self-regulation profiles, both characterized by escalating sleep problems across early childhood and below mean self-regulation. Non-normative group membership was associated with higher teacher-reported hyperactivity and emotional problems, and poorer classroom self-regulation and prosocial skills. CONCLUSION: Early childhood profiles of self-regulation that include sleep problems offer a way to identify children at risk of poor school adjustment. Children with escalating early childhood sleep problems should be considered an important target group for school transition interventions.
Keywords: Children; Child Development -- Sleep; Childhood and child development; Children; Child Development; Sleep; Childhood and child development